SOSIALISASI PEMBUATAN TAHU SEBAGAI PELUANG USAHA DALAM MENINGKATKAN EKONOMI MASYARAKAT KELURAHAN BINTUJU KECAMATAN ANGKOLA MUARATAIS - Nasution, Febriani Hastini; Harahap, Muhammad Syahril; Nasution, Nurhidayah Fithriyah; Siregar, Dedes Asriani; Harahap, Latifa; Riska Indah (Institut Pendidikan Tapanuli Selatan, 2025)
Community Service (PKM). Tofu is a food made from soybeans, the manufacturing process is still simple and traditional. Tofu is very popular and quite enjoyed by the people of Bintuju Village, Angkola Muaratais District, South Tapanuli Regency. Soybeans are relatively cheap and available in all areas and they have existed from the past until now and are still produced. However, the economic condition of craftsmen has not yet progressed significantly. The method that has been carried out in this activity on an ongoing basis is presentation of the material by introducing the ingredients and methods and methods of making tofu, discussion, reflective tofu making practice and evaluation of tofu making activities. Results of Community Service Activities (PKM). This shows that the Bintuju subdistrict community itself has increasingly opened up opportunities to open businesses to increase income. The results of the evaluation or socialization show that the mothers' response to this socialization activity was very positive.. Keywords: Socializationknowledge making.